Research on Residual Life of IGBT Module on EMU in Advanced Repair Based on Power Cycles - JIANG Jie; LI Nan (Kongzhi Yu Xinxi Jishu)
The insulated gate bipolar transistor (IGBT) module is one of the weakest links in the traction converter system. Accurate life and reliability assessment of the IGBT module is particularly important for safe operation of the traction converter system. According to the requirments of whole life cycle assessment of EMU, a research on the life of an advanced repair sample of IGBT module, which is a key component of traction converter, was carried out. Firstly, the influence of thermal stress on module life consumption was studied, and the IGBT module power cycle test was carried out. Then, combined with the test results, the influence of thermal stress on IGBT module life consumption under long-term alternating temperature was studied and characterized, and the deterioration trend of IGBT module performance parameters was analyzed to provide the modeling data. Finally, the mathematical relationship between the deterioration characterization of IGBT module and the lifetime of IGBT module in the converter was deduced, and the lifetime prediction model of IGBT module was established. In this paper, the residual life information of IGBT module was obtained through experiments, and the residual life of IGBT module was evaluated. The failure mechanism of IGBT was found out according to the analysis method of life characteristics, so as to provide a basis for the improvement of maintenance items and the decision-making for maintenance.